STRATEGI PENGEMBANGAN NILAI-NILAI ENTREPRENEURSHIP PADA ANAK USIA DINI - Robi’ah Nugrahani; Erni Munastiwi; Eko Suhendro (Journal of Early Childhood Education (JECE), 2020)
This study aims to explain strategies for developing entrepreneurial values for early childhood. The subjects in this study included teachers, students, and administrators of Kindergarten Khalifah. This research problem was investigated using a qualitative descriptive approach. Observation, interviews, and documentation carried out data collection. The results found in this study are the implementation of strategies for developing early childhood learning models carried out in TK Khalifah Pandeansari in introducing entrepreneurial values. The application of the learning model is also adapted to the stages of early childhood development. Various programs such as market day, outing class, cooking class, and outbound are programs implemented to insert the character of entrepreneurship in children.